Resolução de problemas na licenciatura em matemática: o que apontam os projetos pedagógicos de curso - Silva, Ingrid Pereira da (2021)
This study aims to analyze the organization of the Pedagogical Course Projects of Mathematics Teaching Degrees at Federal Universities and Institutes of RS, regarding the problem-solving approach in the initial training of future mathematics teachers. The interest in the subject is justified by the need to address problem solving as a teaching methodology, especially as a Mathematics Teaching-Learning-Assessment Methodology through RP (MEAAMARP) in the initial training of mathematics teachers, so that approaches with such methodological perspective reach Basic Education. For this investigation, a qualitative and theoretical research is carried out, as it seeks to develop a documental analysis using Bardin's Content Analysis (2011) assumptions to guide the analysis of PCPs. The discussion of the data is guided by the categories of analysis, namely: a) Mathematics Teaching Degree: presence of problem solving in central aspects of the PCP organization; b) Problem solving in subjects of the Mathematics Teaching Degree: concepts of problem solving addressed; c) MEAAMARP: outlining in subjects of the Mathematics Teaching degree courses. In the first category, the study revealed that degree courses indicate the relevance of problem-solving approaches and some aspects related to MEAAMARP and others of mathematics teaching for problem solving. In the second category, it became clear that the PCPs bring indications of the problem-solving approach in School Mathematics subjects, resembling the problem-solving conceptions pointed out by the authors cited in the theoretical review of this work and in Academic Mathematics, including approaches related to mathematics teaching for problem solving. The third category pointed out that in certain School Mathematics subjects there are approximations with the MEAAMARP and with the work including connections through PS. Overall, the discussions, inferences and interpretations carried out showed that the Academic Mathematics subjects focus on teaching undergraduates to apply mathematical concepts and rules in problem solving and that the aspects presented in the School Mathematics subjects can enhance professional development of future mathematics teachers, as they become immersed in problem-solving situations in which they have the opportunity to improve their teaching practice and significantly advance in the understanding of mathematical concepts. However, considering the curriculum of School Mathematics subjects, it is possible that, even studying the objectives of problem solving (about, for and through), discussions are being held in the theoretical field without experiences taking place to articulate theory and practice with each of the objectives indicated. This investigation brings contributions to Mathematical Education, as it points to the need to look at the organization of PCPs in Mathematics Teaching degree courses, regarding the proposition of curricular components that seek approaches with MEAAMARP supported by connections.